Firm productivity in the western Balkans: The impact of European Union membership and access to finance - Howard-Jones P.; Hцlscher J.; Radicic D. (Ekonomski Anali, 2017)
This study examines the productivity performance of Balkan firms within and outside the European Union (EU), including the influence of loans. A multiple treatment model is used to compare the effects on productivity of membership and loans both separately and collectively, which in the case of loans allows a separate analysis of their influence on firms in non-member states. The use of conditional quantile regressions measures the effect on productivity of membership and loans separately as treatment variables. This provides an analysis of where the treatment influence is greatest across the distribution curve and identifies the significance of selected control variables on the outcome. In the full sample, the findings indicate that EU membership and loans have a positive effect on productivity, with membership being more important than loans. Outside the EU, firms in receipt of loans are more productive than those without. However, the significance of both membership and loans is restricted to the lower end of the productivity distribution curve. The manufacturing sample shows that EU membership has a significant positive effect across 70% of the deciles measured, whilst the influence of loans is restricted to the lower deciles, with rental capital (leasing) also positively significant in the lower four deciles. In the services sector, however, membership is significant up to 90% of the distribution, with loans at 60%.